Radial head and neck fractures in children and adolescents - Kalbitz, Miriam; Lackner, Ina; Perl, Mario; Pressmar, Jochen (Frontiers in Pediatrics, 2023)
Background: Radial head and neck fractures are a rare entity in pediatric patients. Due to specific characteristics of the blood supply and remodelling potential, the correct diagnosis and initiation of appropriate therapy are crucial for outcome. Therefore, the aim of this retrospective observational study was to present the outcome of a series of pediatric patients with radial head and neck fractures. Methods: In total 67 pediatric and adolescent patients with a fracture of the proximal radius admitted to a Level I Trauma Center (Germany) between 2005 and 2017 were included in this retrospective observational study. Patients were stratified in accordance to the classification of Judet modified by Metaizeau, as well as in accordance to the AO Pediatric Comprehensive Classification of Long Bone Fractures (AO-PCCF). Results: AO-PCCF fracture type of proximal radius was age dependent. Epiphyseal axis angle and displacement angle correlated significantly. Fractures treated with K-wire or embrochage centromedullaire elastique stable (ECMES) presented higher displacement angles. Duration of callus formation was dependent on both reduction technique and fracture displacement. The range of motion after complete fracture consolidation was dependent on Metaizeau type, reduction technique but independent of duration of immobilization and physical therapy. Conclusion and clinical relevance: Both epiphyseal axis and displacement angle are suitable to measure the initial fracture displacement in radiographs. Consolidation is dependent of the initial displacement and reduction technique. The mini-open approach leads to a worse reduction result, later callus formation and a more restricted range of motion in terms of pronation. Furthermore, the range of motion at follow-up is independent of duration of immobilization and physiotherapy.